KONSEP IMAN KEPADA TAKDIR BAGI DEWASA AKHIR PASCA PENSIUN - Desi Permata Sari; Akhmad Alim; Imas Kania Rahman (Universitas Islam Negeri Alauddin Makassar, 2023)
Late adulthood is an age that has entered the age of 60 years and above and can be called the elderly because the final adult age is at the end of its life limits, at this age, there are many changes that occur in late adulthood including decreased physical strength with health that is not as good as before when enjoying all kinds of world pleasures, The stage of development of late adulthood is also one of them entering retirement and reducing family income. The purpose of this study is to analyze the book of faith in destiny of Muhammad ibn Ibrahim Al-hamd. This research uses qualitative research with a library research approach. The primary data source is the kitab al-iman bil qadha wal qadar by Muhammad ibn Ibrahim Al-Hamd. With technical analysis using literature studies. With the discussion that destiny is divided into destiny that is general, destiny that applies to man, destiny that applies to the age of man, destiny that prevails every year and destiny that prevails daily. Destiny is also divided into sunnatullah and shari'a. With the conclusion that the final adult with the developmental stage reaches retirement when he has faith in a strong destiny will gain the fruit of his faith in performing worship to Allah Swt specifically', staying away from the shirking of the form of small shirk and big shirk, always in hidayah with the addition of faith and guidance from his Rabb, always sincere in the things that have been lived, gaining laughter for his faith, feeling afraid and always being watched by Allah Swt, strong hope and prejudice to Allah Swt, always happy with whatever Allah Swt has set, grateful for whatever Allah Swt has given, gaining joy, knowing the wisdom of Allah Swt for whatever happens, distancing from reason that will plunge into khurafat and spirituality.